1989
DOI: 10.1007/bf01225009
|View full text |Cite
|
Sign up to set email alerts
|

Microcontaminants and reproductive impairment of the Forster's tern on Green Bay, Lake Michigan-1983

Abstract: For the 1983 nesting season, Forster's tern (Sterna forsteri) reproductive success was significantly impaired on organochlorine contaminated Green Bay, Lake Michigan compared to a relatively uncontaminated inland location at Lake Poygan, Wisconsin. Compared with tern eggs from Lake Poygan, eggs from Green Bay had significantly higher median concentrations of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), other polychlorinated dibenzo-p-dioxins (PCDDs), total polychlorinated biphenyls (PCBs), total (three congener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
239
8
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 403 publications
(265 citation statements)
references
References 100 publications
17
239
8
1
Order By: Relevance
“…the attentiveness at the nest of the birds (Peakall & Peakall, 1973;Peakall & Fox, 1987;Scholten et al, 1989). This is difficult to separate from egg mortality caused by contaminant concentrations, without behavioural observations in the colony or egg change experiments between colonies (Kubiak et al, 1989). Both methods were not used in the present study.…”
Section: Increased Mortality Of Embryos and Chicksmentioning
confidence: 98%
See 2 more Smart Citations
“…the attentiveness at the nest of the birds (Peakall & Peakall, 1973;Peakall & Fox, 1987;Scholten et al, 1989). This is difficult to separate from egg mortality caused by contaminant concentrations, without behavioural observations in the colony or egg change experiments between colonies (Kubiak et al, 1989). Both methods were not used in the present study.…”
Section: Increased Mortality Of Embryos and Chicksmentioning
confidence: 98%
“…Only few comparative examples are available, mostly applying to a two-group comparison. For example in Forster's terns (Sterna firsteri), Kubiak et al (1989) found 1 lfold higher TCDD equivalents (in which two PCB congeners accounted for more than 90% of the total) in eggs from a colony with a low hatching success in a heavily contaminated area as compared to eggs from a colony in a relatively clean area where reproduction was normal. In this study, a significant correlation between effect and concentration was found for all six non-planar PCBs analysed, although the correlation coefficients were rather low.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was not found for the C1oA50-200 mg kg -1 group. PCBs have been shown to influence bird behaviour much as parental attentiveness (Kubiak et al, 1989;McArthur et al, 1983), courtship behaviour (Tori & Peterle, 1983) and avoidance behaviour (Kreitzer & Heinz, 1974). The mechanism through which behaviour is influenced is not yet clear.…”
Section: Behaviourmentioning
confidence: 99%
“…In fish-eating birds, exposure to PCBs and related compounds has been associated with effects such as impaired reproduction (Hoffman et al, 1986(Hoffman et al, , 1987Kubiak et al, 1989;Van den Berg et al, 1993), morphological abnormalities (Hoffman et al 1986(Hoffman et al , 1987, thymus atrophy and immunotoxicity (Nikolaidis et al, 1988;Andersson et al, 1991), hypovitaminosis A and/or hypothyroidy (Moccia et al, 1986;Spear et al, 1989;Van den Berg et al, 1993), behaviourial changes (Kubiak et al, 1989;McArthur et al, 1983;Tori & Peterle, 1983), and loss of body weight (Koeman et al, 1973;Gilbertson, 1989). Most of these studies are, however, fieldwork in which it is impossible to make a distinction between effects caused by PCBs and those caused by other substances such as polycyclic aromatic hydrocarbons (PAHs).…”
mentioning
confidence: 99%